A cost-effective and high-efficiency online ED-BMED integrated system enables the conversion of 3.5 wt% NaCl aqueous solution into 6.20 mol/L NaOH. (15th April 2023) - Fu, Rong; Wang, Huangying; Yan, Junying; Li, Ruirui; Wang, Baoying; Jiang, Chenxiao; Wang, Yaoming; Xu, Tongwen
Graphical abstract: Highlights: 3.5 wt% NaCl was converted into 6.20 M NaOH using online integrated ED-BMED; BMED + ED has a limit for base concentration up to 5.35 mol/L; Online ED-BMED integration is more competitive than BMED and BMED + ED; Sufficient salt supply enables high current water splitting in bipolar membranes; Abstract: Resource recycling has been identified as an important concept for the development of a circular economy. Brine, which is widely generated from various industrial wastewater treatment facilities, is a promising treasure trove of resources. Previously, bipolar membrane electrodialysis (BMED) has been attempted to valorize brine into more valuable soda. However, the relatively low concentration of recycled base, typically lower than 4.0 mol/L, has restricted the promotion of this technology to a large extent. Herein, in this study, electrodialysis (ED) and BMED were successfully coupled in an online integrated system to increase the generated base concentration. The concentration function in ED could provide sufficient feedstock for BMED, which creates the possibility for high-efficiency water splitting in the bipolar membrane at extremely high current densities. This integrated ED-BMED system enables the production of 6.20 mol/L NaOH, a highly recorded base concentration that has not been reported. To assess the flexibility of this online combination system, the ED-BMED was compared with conventional BMED and a BMED + ED (acid/base production by BMED followed by concentration using ED) system; it was found that the apparent or total energy consumption in ED-BMED was less than that in the latter two. Thus, this ED-BMED integrated system achieves the one-step conversion of low concentration brine into a highly concentrated base with a low energy consumption and has a high potential for industrial applications.